“Understand It First!” Pedagogical and Assessment Practices with SOLO Taxonomy: An Overview on an Experimental Research Study - Bhagwat, Minaxi S.; Kothari, R. G. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
CASE- Dept. of Education, Faculty of Education and Psychology, the Maharaja Sayajirao University of Baroda, Vadodara.